ICURE (iterative course‐based undergraduate research experience): A case‐study. Issue 5 (1st July 2019) - Stoeckman, Angela K.; Cai, Yingqi; Chapman, Kent D.
Abstract: Several models suggest ways to expose undergraduates at minority serving institutions or institutions with limited research infrastructures to the iterative process of research. Apprentice‐based research experiences allow students to work one‐on‐one with a research mentor in the hands‐on discovery process, but with teaching being a priority for faculty at the aforementioned institutions, financial, spatial, and time limitations for research progress exist. Course‐based undergraduate research experiences (CUREs) provide opportunities for a greater number of undergraduates to become familiar with the questions, techniques, and failure involved in research. However, designing projects that a group of students can complete in a semester can be challenging. Inclusive Research Education Communities are intended to promote retention in STEM courses for early college students but have limited benefit for upper‐level courses. We sought to create an iterative CURE between fall semester BIOL3900 at the University of North Texas and spring semester CHE397 at Bethel University (Saint Paul, MN) to promote collaboration between unique learning communities. The research goal was to use a tobacco ( Nicotiana benthamiana ) transient expression system as a platform to test gene functions and to engineer valuable bioproducts in plant vegetative tissues. The outcomes of this 2‐year integrative module included novel discoveries leading to publications in peer‐reviewed journals, cost benefits due to shared resources, continual movement of the project, course‐based training for future independent research projects, and improved student attitudes about research. © 2019 International Union of Biochemistry and Molecular Biology, 47(5):565–572, 2019.